Phase change magnetic fluid, preparation method and application thereof, and method for absorbing and desorbing carbon dioxide

CN122537913BActive Publication Date: 2026-10-27UNIV OF SCI & TECH BEIJING +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611041869.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-27
Estimated Expiration
2046-07-14

AI Technical Summary

Technical Problem

[0010]本发明的目的是为了克服现有技术存在的CO2高温解吸过程中吸收剂易降解的问题,提供一种相变磁流体及其制备方法和应用、二氧化碳的吸收与解吸的方法

Benefits of technology

(1)本发明中,所述相变磁流体包括具有特定聚合物的聚合物水凝胶和分散在聚合物水凝胶内部的改性磁性纳米粒子,并且限定了改性磁性纳米粒子的平均粒径,特定平均粒径的改性磁性纳米粒子通过氢键、静电作用与聚合物水凝胶紧密结合,使得所述相变磁流体具有磁感应致热特点,有利于实现交变磁场作用下的靶向升温解吸;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122537913B_ABST
    Figure CN122537913B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of carbon dioxide capture and regeneration, and discloses a phase-change magnetic fluid and a preparation method and application thereof, and a carbon dioxide absorption and desorption method. The phase-change magnetic fluid comprises a polymer hydrogel and modified magnetic nanoparticles uniformly dispersed in the polymer hydrogel; the polymer in the polymer hydrogel has a structural unit A shown in formula I, a structural unit B shown in formula II and / or formula III, and a structural unit C provided by a crosslinking agent containing at least two unsaturated double bonds; formula I; formula II; formula III; R1, R5, R6 and R7 are each independently H or C1-C4 alkyl, R2 is C1-C6 alkylene, R3 and R4 are each independently C1-C4 alkyl, and R8 is C3-C7 alkylene; and the average particle size of the modified magnetic nanoparticles is 20-100 nm. The phase-change magnetic fluid can realize reversible capture and release of CO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of carbon dioxide capture and regeneration technology, specifically to a phase change magnetofluid and its preparation method and application, as well as a method for carbon dioxide absorption and desorption. Background Technology

[0002] Currently, carbon dioxide capture and absorbents used in industrial applications and existing research generally suffer from several technical defects. In particular, the three most prominent problems are high regeneration energy consumption, poor cycle stability, and high volatility that easily leads to secondary pollution. These problems severely restrict the large-scale industrial application of carbon dioxide capture and storage (CCUS) technology and the control of decarbonization costs, making it difficult to meet the actual needs of long-term continuous and stable operation.

[0003] I. The energy consumption for absorbent regeneration is too high, resulting in poor economic efficiency of the decarbonization process. Excessive regeneration energy consumption is the most significant technical bottleneck of existing CO2 absorbents. Among them, the most widely used chemical amine absorbents, including traditional alkyl alcohol amines such as monoethanolamine (MEA) and diethanolamine (DEA) and mixed amine systems, have a strong binding force with carbon dioxide. Their desorption and regeneration require high-pressure steam heating at 100-120℃, and this part of the energy consumption accounts for 60%-80% of the total energy consumption of the entire capture system, which significantly increases the cost of carbon dioxide capture.

[0004] Although phase change absorbents and liquid-liquid separation solvents can theoretically reduce energy consumption by regenerating only the carbon dioxide-rich phase through phase separation, the actual desorption temperature still needs to be 80-100℃. They cannot be separated from the high-temperature heat source and require additional supporting separation equipment. At the same time, high-temperature regeneration will aggravate water evaporation and increase the energy consumption for water vapor recovery. Therefore, it is still impossible to achieve low-energy consumption and low-cost decarbonization.

[0005] II. The absorbent has poor cycle stability and its performance degrades significantly with long-term use. Existing carbon dioxide absorbents exhibit significant performance degradation during recycling and lack long-term operational stability, failing to meet the continuous capture requirements of industrial scenarios. Chemical amine absorbents, under high-temperature regeneration conditions and the combined effects of impurities such as oxygen, sulfur oxides, and nitrogen oxides in industrial flue gas, are prone to oxidative degradation and thermal aging, generating inert byproducts. This leads to the loss of effective absorbent components and a substantial decrease in CO2 capture capacity and mass transfer efficiency. After several months of continuous operation, the capture efficiency can drop by 15%-30%, requiring frequent replenishment of fresh solvent to maintain normal operation.

[0006] Phase change absorbents and composite modified absorbents have poorer cycle stability. Long-term alternating hot and cold operation can easily lead to phase separation failure and active component precipitation. Some absorbents can also be irreversibly combined with flue gas dust and acidic impurities, resulting in poisoning and inactivation. In addition, most absorbents are poorly adaptable to fluctuations in industrial flue gas conditions and are difficult to adapt to the actual flue gas environment of non-steady state and high impurities, thus limiting their large-scale application.

[0007] Third, the absorbent is highly volatile and can easily cause secondary pollution and equipment damage. Existing conventional carbon dioxide absorbents have high vapor pressures, resulting in significant volatilization losses during capture and regeneration. This not only wastes the absorbent but also easily leads to secondary pollution. Small molecule alkyl alcohol amine absorbents are particularly volatile, and during capture, they are emitted with the purified flue gas, forming amine aerosols and volatile organic compounds (VOCs), polluting the surrounding atmosphere. During regeneration, the volatilized active components enter the water circulation system with the condensate, easily causing nitrogen pollution in water bodies. Additional waste gas and wastewater treatment devices are required, increasing process complexity and operation and maintenance costs.

[0008] Modified polymer absorbents and phase change solvents cannot completely eliminate the volatilization problem. During long-term operation, the active components slowly volatilize, which will damage the stability of the system. Furthermore, the volatilization degradation products combine with flue gas impurities, which can easily cause equipment blockage, aggravate equipment corrosion, and shorten the service life of the equipment.

[0009] In summary, existing carbon dioxide absorbents generally suffer from core defects such as high regeneration energy consumption, poor cycle stability, and high volatility, which can easily lead to secondary pollution. This makes it difficult to simultaneously achieve high decarbonization efficiency, economic efficiency, and environmental friendliness. Therefore, developing new green and efficient absorbents that combine low regeneration energy consumption, high cycle stability, and low volatility is key to overcoming the current bottlenecks in CCUS technology and promoting its industrial application. Summary of the Invention

[0010] The purpose of this invention is to overcome the problem of easy degradation of absorbents during high-temperature CO2 desorption in existing technologies, and to provide a phase change magnetic fluid, its preparation method and application, and a method for the absorption and desorption of carbon dioxide. This phase change magnetic fluid exhibits excellent cycle stability and a high desorption rate. Based on the magnetocaloric effect generated by modified magnetic nanoparticles in the phase change magnetic fluid in an alternating magnetic field, localized and controllable heating is achieved to trigger the phase change of the polymer hydrogel and realize CO2 release. Furthermore, by employing an alternating magnetic field with specific parameters, the energy consumption for heating the exchange magnetic field is low, enabling reversible capture and release of CO2 while maintaining a low overall heat load.

[0011] To achieve the above objectives, the first aspect of the present invention provides a phase change magnetic fluid, wherein the phase change magnetic fluid comprises a polymer hydrogel and modified magnetic nanoparticles uniformly dispersed within the polymer hydrogel. The polymer in the polymer hydrogel has structural unit A as shown in Formula I, structural unit B as shown in Formula II and / or Formula III, and structural unit C provided by a crosslinking agent containing at least two unsaturated double bonds; , Formula I; Formula II; Formula III; R1, R5, R6, and R7 are each independently H or C1-C4 alkyl groups, R2 is a C1-C6 alkylene group, R3 and R4 are each independently C1-C4 alkyl groups, and R8 is a C3-C7 alkylene group. The modified magnetic nanoparticles have an average particle size of 20-100 nm.

[0012] A second aspect of the present invention provides a method for preparing a phase change magnetic fluid, wherein the preparation method includes the following steps: S1. In the presence of a solvent, a polymeric monomer, a crosslinking agent containing at least two unsaturated double bonds, a first surfactant, and an initiator are first mixed and then subjected to a copolymerization reaction, followed by post-treatment; the polymeric monomer includes monomer A shown in Formula 1, monomer B shown in Formula 2 and / or Formula 3; Equation 1; Equation 2; Equation 3; R1', R5', R6', and R7' are each independently H or C1-C4 alkyl groups, R2' is a C1-C6 alkylene group, R3' and R4' are each independently C1-C4 alkyl groups, and R8' is a C3-C7 alkylene group. S2. Modified magnetic nanoparticles are added to the product obtained in step S1, and a second mixing is performed to obtain a phase change magnetic fluid. The modified magnetic nanoparticles have an average particle size of 20-100 nm.

[0013] A third aspect of the present invention provides a phase change magnetofluid obtained by the preparation method described in the second aspect above.

[0014] The fourth aspect of the present invention provides the application of the phase change magnetofluid provided by the first or third aspect above as a carbon dioxide absorbent in CO2 emission reduction, carbon capture in biomass utilization processes, or direct carbon capture in air.

[0015] A fifth aspect of the present invention provides a method for the absorption and desorption of carbon dioxide, wherein the method includes: Step 1: Absorb CO2-containing gas mixture in the presence of phase change magnetohydrodynamic fluid; Step 2: In the presence of an alternating magnetic field, the phase change magnetofluid processed in Step 1 is desorbed. Step 3: After desorption is completed, stop the alternating magnetic field to complete the first cycle of absorption and desorption. Then repeat steps 1 and 2. The phase change magnetic fluid is the phase change magnetic fluid provided in the first or third aspect above; The conditions for the alternating magnetic field include: magnetic induction intensity ≥1400GS, and magnetic field frequency of 500-800kHz.

[0016] Through the above technical solutions, the phase change magnetofluid, its preparation method and application, and the method for carbon dioxide absorption and desorption provided by the present invention achieve the following beneficial effects: (1) In this invention, the phase change magnetic fluid includes a polymer hydrogel with a specific polymer and modified magnetic nanoparticles dispersed inside the polymer hydrogel, and the average particle size of the modified magnetic nanoparticles is defined. The modified magnetic nanoparticles with a specific average particle size are tightly bound to the polymer hydrogel through hydrogen bonds and electrostatic interactions, so that the phase change magnetic fluid has the characteristics of magnetic induction heating, which is beneficial to achieving targeted heating and desorption under the action of alternating magnetic field. (2) In this invention, a phase change magnetic fluid is obtained by mixing a specific monomer with modified magnetic nanoparticles of a specific average particle size after polymerization. Based on the magnetocaloric effect generated by the modified magnetic nanoparticles in the phase change magnetic fluid in an alternating magnetic field, the phase change magnetic fluid is locally and controllably heated to trigger the phase change of the polymer hydrogel and realize CO2 release. Furthermore, by using an alternating magnetic field with specific adjustable parameters, the magnetocaloric heat generation rate can be precisely controlled to achieve the desorption temperature regulation within a small range. It can both rapidly heat up to trigger desorption and reduce the desorption rate by lowering the magnetic field parameters to meet the desorption rhythm requirements under different working conditions, and achieve controllable desorption of CO2 while maintaining a low overall heat load. (3) In this invention, the method for the absorption and desorption of carbon dioxide is much faster than the traditional steam heating method which relies on steam heating and the pure gel system as a whole. The desorption response is extremely fast using a high-frequency alternating magnetic field. (4) The local heating characteristics of modified magnetic nanoparticles in phase change magnetofluid induced by alternating magnetic field avoid the sensible heat loss of traditional overall heating; at the same time, rapid phase change desorption reduces the exposure time of the magnetofluid at high temperature, further reducing energy waste and achieving the synergy of "rapid response" and "low energy consumption". (5) Modified magnetic nanoparticles are tightly bound to the polymer hydrogel through hydrogen bonds and electrostatic interactions, resulting in no particle loss or aggregation of the phase change magnetic fluid under a high-frequency magnetic field. The phase change magnetic fluid exhibits a low CO2 absorption capacity decay rate after multiple cycles, which is far superior to the traditional amine method. Furthermore, the magnetothermal desorption process is mild. The gel system being at a very high temperature would lead to gel degradation, while magnetic induction heating is only partial and in-situ heating, which can avoid gel degradation and amine oxidation caused by high temperature. The polymer skeleton of the liquid phase change nanogel has strong chemical inertness and does not react with SO2. X NO X When acidic gases react, SO in the flue gas... X NO X It has stronger tolerance to impurities and is more widely applicable in industry. Attached Figure Description

[0017] Figure 1 This refers to the temperature control experiment of phase change magnetofluid in alternating magnetic field in Example 1; Figure 2 It is the absorption capacity of the phase change magnetofluid in Example 1 after ten absorption-desorption cycles. Detailed Implementation

[0018] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0019] To achieve the above objectives, the first aspect of the present invention provides a phase change magnetic fluid, wherein the phase change magnetic fluid comprises a polymer hydrogel and modified magnetic nanoparticles uniformly dispersed within the polymer hydrogel. The polymer in the polymer hydrogel has structural unit A as shown in Formula I, structural unit B as shown in Formula II and / or Formula III, and structural unit C provided by a crosslinking agent containing at least two unsaturated double bonds; , Formula I; Formula II; Formula III; R1, R5, R6, and R7 are each independently H or C1-C4 alkyl groups, R2 is a C1-C6 alkylene group, R3 and R4 are each independently C1-C4 alkyl groups, and R8 is a C3-C7 alkylene group. The modified magnetic nanoparticles have an average particle size of 20-100 nm.

[0020] In this invention, the phase change magnetic fluid includes a polymer hydrogel with a specific polymer and modified magnetic nanoparticles dispersed inside the polymer hydrogel, which gives the phase change magnetic fluid the characteristics of magnetic induction heating, which is beneficial for achieving targeted heating and desorption under the action of an alternating magnetic field.

[0021] More preferably, R1, R5, R6, and R7 are each independently an H or C1-C3 alkyl group.

[0022] More preferably, R2 is a C3-C6 alkylene group.

[0023] More preferably, R3 and R4 are each independently a C1-C3 alkyl group.

[0024] More preferably, R8 is a C3-C6 alkylene group.

[0025] In this invention, the crosslinking agent has at least two unsaturated double bonds. Preferably, the crosslinking agent is selected from at least one of N,N'-methylenebisacrylamide, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, divinyl sulfone, and trimethylolpropane triacrylate.

[0026] According to the present invention, preferably, the modified magnetic nanoparticles include a modifier and unmodified magnetic nanoparticles.

[0027] In this invention, there is no particular limitation on the type of unmodified magnetic nanoparticles, which can be those conventionally used in the art. Preferably, the unmodified magnetic nanoparticles are selected from at least one of Fe3O4, Co3O4, γ-Fe2O3, MnFe2O4, CoFe2O4, ZnFe2O4 and NiFe2O4.

[0028] According to the present invention, preferably, the content of the modifier is 0.2-2 wt%, based on the total mass of the modified magnetic nanoparticles. For example, it can be 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt%, 2 wt%, or any value within any range of any two values, preferably 0.5-1.5 wt%. The content of unmodified magnetic nanoparticles is 98-99.8 wt%, for example, it can be 98 wt%, 98.1 wt%, 98.2 wt%, 98.3 wt%, 98.4 wt%, 98.5 wt%, 98.6 wt%, 98.7 wt%, 98.8 wt%, 98.9 wt%, 99 wt%, 99.1 wt%, 99.2 wt%, 99.3 wt%, 99.4 wt%, 99.5 wt%, 99.6 wt%, 99.7 wt%, 99.8 wt%, or any value within any range of any two values, preferably 98.5-99.5 wt%.

[0029] In this invention, the content of the modifier and the unmodified magnetic nanoparticles is within the above-mentioned preferred range, which is beneficial to further trigger the phase change of the polymer hydrogel and realize CO2 release.

[0030] In this invention, the content of the modifier and the content of the unmodified magnetic nanoparticles are obtained by thermogravimetric analysis.

[0031] In one specific embodiment of the present invention, the method for preparing unmodified magnetic nanoparticles includes, but is not limited to: Step I: Mix the solution of the precursor containing the metal element with a second surfactant to obtain mixture I; Step II: Under a protective atmosphere, mixture I is optionally heated, and then a precipitant is added to bring the pH to 9-12. After aging, unmodified magnetic nanoparticles are obtained.

[0032] In this invention, the precursor containing the metal element can be any soluble compound that can provide the corresponding valence metal ion in the unmodified magnetic nanoparticles, and this invention does not have any particular limitation on this.

[0033] The present invention allows for a wide range of selection for the concentration of metal elements in the solution of the precursor containing metal elements, as long as the particle size described above can be obtained. Those skilled in the art can make selections according to actual needs. Preferably, the concentration of metal elements in the solution of the precursor containing metal elements is 0.1-1 mol / L.

[0034] According to the present invention, preferably, the second surfactant is oleic acid, and the volume fraction of oleic acid is 0.1-5% based on the total volume of mixture I.

[0035] According to the present invention, preferably, the heating conditions include: a temperature of 50-90°C and a time of 30-240 min.

[0036] The present invention allows for a wide range of choices of precipitants; preferably, the precipitant is ammonia.

[0037] The present invention allows for a wide range of selection for the addition rate of the precipitant. Preferably, the addition rate of the precipitant is 0.5-3 mL / min.

[0038] According to the present invention, preferably, the aging conditions include: a temperature of 70-200°C and a time of 0.5-8 hours.

[0039] According to the present invention, preferably, step 2 after aging also includes a first separation and a first washing.

[0040] In one specific embodiment of the present invention, the method for preparing the modified magnetic nanoparticles includes, but is not limited to: The solution containing unmodified magnetic nanoparticles was mixed with a modifier for modification.

[0041] According to the present invention, preferably, the modifier is selected from at least one of methoxy polyethylene glycol silane, sodium carboxyethyl silane triol, sulfonate silane coupling agent, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, citric acid, and 3-mercaptopropyltriethoxysilane.

[0042] In this invention, preferably, the amount of the modifier and the unmodified magnetic nanoparticles is such that, based on the total mass of the modified magnetic nanoparticles, the content of the modifier is 0.2-2 wt% and the content of the unmodified magnetic nanoparticles is 98-99.8 wt%.

[0043] In this invention, using the aforementioned preferred range is beneficial for modifying magnetic nanoparticles with modifiers, avoiding insufficient hydrophilic group loading and poor dispersibility improvement due to too low a modifier dosage, and preventing excessive particle surface coating and particle aggregation and adhesion due to too high a modifier dosage. At the same time, it reduces the residue of free modifiers and lowers the difficulty of subsequent purification.

[0044] More preferably, the amounts of the modifier and the unmodified magnetic nanoparticles are such that, based on the total mass of the modified magnetic nanoparticles, the content of the modifier is 0.5-1.5 wt% and the content of the unmodified magnetic nanoparticles is 98.5-99.5 wt%.

[0045] The present invention has a wide range of options for modification conditions. Preferably, the modification conditions include: a temperature of 50-100℃ and a time of 1-8h.

[0046] In this invention, the modified material further includes a second separation and a second washing.

[0047] The present invention has a wide range of options for the conditions and methods of the first separation, the first washing, the second separation, and the second washing. As long as impurities can be separated and removed to obtain modified magnetic nanoparticles with the particle size described above, it is acceptable. Those skilled in the art can make selections according to actual needs. For example, the first separation and the second separation can be magnetic separation and / or centrifugal separation.

[0048] According to a preferred embodiment of the present invention, the second washing may or may not involve drying; preferably, the second washing is not followed by drying.

[0049] In this invention, the average particle size of the modified magnetic nanoparticles is 20-100 nm, for example, it can be 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, 32 nm, 34 nm, 36 nm, 38 nm, 40 nm, 42 nm, 44 nm, 46 nm, 48 nm, 50 nm, 52 nm, 54 nm, 56 nm, 58 nm, 60 nm, 62 nm, 64 nm, 66 nm, 68 nm, 70 nm, 72 nm, 74 nm, 76 nm, 78 nm, 80 nm, 82 nm, 84 nm, 86 nm, 88 nm, 90 nm, 92 nm, 94 nm, 96 nm, 98 nm, 100 nm, or any value within any range of two such values, preferably 20-60 nm.

[0050] In this invention, unmodified magnetic nanoparticles are modified with a specific modifier, and the average particle size of the modified magnetic nanoparticles is further controlled. This ensures that the modified magnetic nanoparticles are uniformly dispersed within the polymer hydrogel, which helps to ensure the overall composition of the polymer hydrogel system is uniform, and that the mechanical and magnetic response properties are stable and balanced. It also avoids uneven stress and decreased magnetic response sensitivity within the gel due to local particle agglomeration and accumulation. At the same time, it ensures that the nanoparticles are tightly bonded to the gel matrix, making it less prone to phase separation and particle sedimentation, and effectively improving the phase change magnetic fluid's resistance to interference from flue gas impurities.

[0051] According to the present invention, preferably, based on the total amount of the polymer hydrogel, the content of structural unit A is 2-65 mol; the content of structural unit B is 20-90 mol; and the content of structural unit C is 2-30 mol.

[0052] In this invention, when the content of each structural unit of the polymer in the polymer hydrogel meets the above-mentioned range, it is beneficial to construct a polymer hydrogel matrix with moderate crosslinking density and uniform and regular network structure.

[0053] More preferably, based on the total amount of the polymer hydrogel, the content of structural unit A is 4-60 mol%, the content of structural unit B is 25-80 mol%, and the content of structural unit C is 4-20 mol.

[0054] More preferably, based on the total amount of the polymer hydrogel, the content of structural unit A is 5-50 mol%, the content of structural unit B is 30-75 mol%, and the content of structural unit C is 5-15 mol.

[0055] In this invention, the content of each structural unit of the polymer in the polymer hydrogel is determined by nuclear magnetic resonance spectroscopy. 1 H-NMR and 13 Measured by C-NMR.

[0056] According to the present invention, preferably, the polymer hydrogel has an intrinsic viscosity of 300-1800 mL / g at 25°C.

[0057] In this invention, the intrinsic viscosity of the polymer hydrogel at 25°C was obtained by capillary Ubbelohde viscometer method.

[0058] More preferably, the intrinsic viscosity of the polymer hydrogel at 25°C is 600-1500 mL / g.

[0059] According to the present invention, preferably, based on the total weight of the phase change magnetic fluid, the content of the polymer hydrogel is 99-99.9 wt%, and the content of the modified magnetic nanoparticles is 0.01-1 wt%.

[0060] In this invention, when the content of polymer hydrogel and modified magnetic nanoparticles in the phase change magnetic fluid meets the above-mentioned range, particle agglomeration and phase separation can be avoided inside the phase change magnetic fluid system, while improving the magnetic response performance, system stability and resistance to interference from flue gas impurities of the phase change magnetic fluid.

[0061] More preferably, based on the total weight of the phase change magnetic fluid, the content of the polymer hydrogel is 99.5-99.95 wt%, and the content of the modified magnetic nanoparticles is 0.05-0.5 wt%.

[0062] More preferably, based on the total weight of the phase change magnetic fluid, the content of the polymer hydrogel is 99.75-99.9 wt%, and the content of the modified magnetic nanoparticles is 0.1-0.25 wt%.

[0063] In this invention, the contents of polymer hydrogel and modified magnetic nanoparticles in the phase change magnetofluid are calculated by precision balance weighing.

[0064] A second aspect of the present invention provides a method for preparing a phase change magnetic fluid, wherein the preparation method includes the following steps: S1. In the presence of a solvent, a polymeric monomer, a crosslinking agent containing at least two unsaturated double bonds, a first surfactant, and an initiator are first mixed and then subjected to a copolymerization reaction, followed by post-treatment; the polymeric monomer includes monomer A shown in Formula 1, monomer B shown in Formula 2 and / or Formula 3; Equation 1; Equation 2; Equation 3; R1', R5', R6', and R7' are each independently H or C1-C4 alkyl groups, R2' is a C1-C6 alkylene group, R3' and R4' are each independently C1-C4 alkyl groups, and R8' is a C3-C7 alkylene group. S2. Modified magnetic nanoparticles are added to the product obtained in step S1, and a second mixing is performed to obtain a phase change magnetic fluid. The modified magnetic nanoparticles have an average particle size of 20-100 nm.

[0065] In this invention, the product obtained by copolymerization of a specific monomer is mixed with modified magnetic nanoparticles of a specific average particle size to obtain a phase change magnetic fluid. The modified magnetic nanoparticles are uniformly dispersed in the phase change magnetic fluid. The resulting phase change magnetic fluid has the characteristics of sensitive and rapid magnetic response, controllable phase change behavior, excellent dispersion stability, no particle agglomeration and sedimentation, and strong resistance to impurity interference. This is beneficial to ensure the overall system performance is balanced and stable, and to extend the product's cycle life.

[0066] More preferably, R1', R5', R6', and R7' are each independently an H or C1-C3 alkyl group.

[0067] More preferably, R2' is a C3-C6 alkylene group.

[0068] More preferably, R3' and R4' are each independently a C1-C3 alkyl group.

[0069] More preferably, R8' is a C3-C6 alkylene group.

[0070] According to the present invention, preferably, the amount of monomer A is 2-65 mol; the amount of monomer B is 20-90 mol; and the amount of crosslinking agent is 2-30 mol.

[0071] In this invention, when the amounts of monomer A, monomer B, and crosslinking agent meet the above-mentioned ranges, it is beneficial to form a polymer hydrogel network with uniform crosslinking and regular structure.

[0072] More preferably, the amount of monomer A is 4-60 mol; the amount of monomer B is 25-80 mol; and the amount of crosslinking agent is 4-20 mol.

[0073] More preferably, the amount of monomer A is 5-65 mol%, preferably 5-50 mol; the amount of monomer B is 30-90 mol%, preferably 30-75 mol; and the amount of crosslinking agent is 5-20 mol%, preferably 5-15 mol.

[0074] In some specific embodiments of the present invention, preferably, the solvent is water and / or a C1-C4 alcohol, preferably deionized water. Using the aforementioned preferred solvent helps to ensure a mild and pure reaction environment, avoids the influence of residual organic solvents on component compatibility, and is suitable for the dispersion of hydrophilic modified magnetic nanoparticles, preventing particle aggregation and ensuring that the reaction and blending process is stable and controllable.

[0075] In this invention, the crosslinking agent has at least two unsaturated double bonds. Preferably, the crosslinking agent is selected from at least one of N,N'-methylenebisacrylamide, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, divinyl sulfone, and trimethylolpropane triacrylate.

[0076] In this invention, there is no particular limitation on the type of the first surfactant. It can be any hydrophilic first surfactant commonly used in the art. Preferably, the first surfactant is selected from at least one of hexadecyltrimethylammonium bromide, benzalkonium chloride, hexadecylpyridine chloride, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, octadecyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride, tetradecyldimethylbenzylammonium chloride, and octadecyldimethylbenzylammonium bromide.

[0077] According to the present invention, preferably, the amount of the first surfactant is 0.4-2 mol%, more preferably 0.5-2 mol%, and more preferably 0.6-2 mol%, based on the total amount of the polymer monomers.

[0078] According to the present invention, preferably, the first mixing is carried out in the presence of an inert gas and / or nitrogen.

[0079] According to the present invention, preferably, the conditions for the first mixing include: a temperature of 50-90°C and a time of 10-60 min.

[0080] More preferably, the conditions for the first mixing include: a temperature of 60-80°C and a time of 15-45 minutes.

[0081] More preferably, the conditions for the first mixing include: a temperature of 65-75°C and a time of 20-40 minutes.

[0082] According to the present invention, preferably, the initiator is a water-soluble initiator and / or an oil-soluble initiator, more preferably a water-soluble azo initiator and / or an oil-soluble azo initiator, and more preferably a water-soluble azo initiator.

[0083] According to the present invention, preferably, the oil-soluble azo initiator is selected from azobisisobutyronitrile and / or azobisisoheptanenitrile.

[0084] According to the present invention, preferably, the water-soluble azo initiator is selected from 2,2'-azobisisobutylamidine dihydrochloride and / or azobisisobutylimidazoline hydrochloride.

[0085] According to the present invention, preferably, the amount of initiator is 0.1-5 mol%, based on the total amount of the polymerizable monomers. Using the aforementioned preferred amount of initiator helps to ensure a moderate polymerization rate and complete reaction, avoids uneven molecular weight distribution of polymer due to excessive initiator, or incomplete polymerization due to insufficient initiator, thereby ensuring a uniform gel network structure and uniform dispersion of modified magnetic nanoparticles after mixing.

[0086] More preferably, based on the total amount of the polymerizable monomers, the amount of the initiator is 0.8-2 mol%, more preferably 0.8-1.7 mol.

[0087] According to the present invention, preferably, the copolymerization reaction is carried out in the presence of an inert gas and / or nitrogen.

[0088] According to the present invention, preferably, the copolymerization reaction conditions include: a temperature of 50-90°C and a time of 60-300 min.

[0089] More preferably, the copolymerization reaction conditions include: a temperature of 60-85°C and a time of 90-250 min.

[0090] More preferably, the copolymerization reaction conditions include: a temperature of 65-80°C and a time of 120-200 min.

[0091] In this invention, it is preferable that both the first mixing and copolymerization reactions are carried out in the presence of stirring.

[0092] In this invention, there are no particular limitations on the post-treatment operation, as long as the small molecule impurities and the first surfactant in the reaction system can be removed. In some specific embodiments of this invention, deionized water dialysis is used for treatment. Specifically, the deionized water dialysis treatment time is ≥3 days, and the water is changed ≥3 times a day.

[0093] According to a preferred embodiment of the present invention, the product obtained in step S1 is in the state of a solution, preferably a milky white homogeneous solution.

[0094] In this invention, the types of modified magnetic nanoparticles and the preparation methods of the modified magnetic nanoparticles are as described above, and will not be repeated here.

[0095] According to the present invention, preferably, based on the total amount of the phase change magnetofluid, the content of the modified magnetic nanoparticles is 0.01-1 wt%, and the amount of the product obtained in step S1 is 99-99.9 wt%.

[0096] In this invention, when the content of the modified magnetic nanoparticles meets the above-mentioned range, it is beneficial to achieve uniform loading of particles in the gel network, avoid particle agglomeration due to excessive dosage, and insufficient magnetic response due to insufficient dosage, thereby synergistically improving the magnetic response sensitivity and long-term stability of the phase change magnetic fluid.

[0097] More preferably, based on the total amount of the phase change magnetofluid, the amount of the modified magnetic nanoparticles is 0.05-0.5 wt%, more preferably 0.1-0.25 wt%.

[0098] More preferably, based on the total amount of the phase change magnetofluid, the amount of the product obtained in step S1 is 99.5-99.95 wt%, preferably 99.75-99.9 wt%.

[0099] In this invention, there is no particular limitation on the second mixing method, which can be any conventional means in the art, as long as the modified magnetic nanoparticles are uniformly dispersed in the product obtained in step S1. In some specific embodiments of this invention, preferably, ultrasonic treatment can be used to fully mix the modified magnetic nanoparticles with the product obtained in step S1.

[0100] In one specific embodiment of the present invention, an ultrasonic cell disruptor or ultrasonic disperser is used to process the system, and the specific ultrasonic time can be selected according to the actual situation.

[0101] In this invention, the preparation method further includes degassing the ultrasonically treated system, for example, vacuum degassing or static degassing can be selected, as long as the purpose of this invention can be achieved.

[0102] A third aspect of the present invention provides a phase change magnetofluid obtained by the preparation method described in the second aspect above.

[0103] The fourth aspect of the present invention provides the application of the phase change magnetofluid provided by the first or third aspect above as a carbon dioxide absorbent in CO2 emission reduction, carbon capture in biomass utilization processes, or direct carbon capture in air.

[0104] A fifth aspect of the present invention provides a method for the absorption and desorption of carbon dioxide, wherein the method includes: Step 1: Absorb CO2-containing gas mixture in the presence of phase change magnetohydrodynamic fluid; Step 2: In the presence of an alternating magnetic field, the phase change magnetofluid processed in Step 1 is desorbed. Step 3: After desorption is completed, stop the alternating magnetic field to complete the first cycle of absorption and desorption. Then repeat steps 1 and 2. The phase change magnetic fluid is the phase change magnetic fluid provided in the first or third aspect above; The conditions for the alternating magnetic field include: magnetic induction intensity ≥1400GS, and magnetic field frequency of 500-800kHz.

[0105] In this invention, localized and controllable heating is achieved based on the magnetocaloric effect generated by modified magnetic nanoparticles in the phase change magnetofluid under an alternating magnetic field, thereby triggering the phase change of the polymer hydrogel and realizing CO2 release. Furthermore, by using an alternating magnetic field with specific parameters, the magnetocaloric heat generation rate can be precisely controlled, and the desorption temperature can be adjusted within ±2℃. This allows for rapid temperature rise to trigger desorption, and the desorption rate can be reduced by lowering the magnetic field parameters to meet the desorption rhythm requirements under different operating conditions, and to achieve controllable CO2 desorption while maintaining a low overall heat load.

[0106] More preferably, the conditions for the alternating magnetic field include: magnetic induction intensity ≥1500GS, more preferably 1500-1800GS; and magnetic field frequency 600-800kHz.

[0107] According to the present invention, preferably, the temperature of the absorption treatment is 20-50°C.

[0108] More preferably, the absorption treatment temperature is 25-45°C.

[0109] More preferably, the absorption treatment temperature is 30-40°C.

[0110] In this invention, there is no particular limitation on the absorption treatment time; it can be selected according to the actual situation, as long as the purpose of this invention can be achieved.

[0111] In this invention, the CO2-containing gas mixture is sourced from Beijing Haipu Gas Co., Ltd.

[0112] According to the present invention, preferably, the CO2 content in the CO2-containing gas mixture is 0.04-30 vol%, more preferably 5-20 vol%.

[0113] According to the present invention, preferably, the temperature of the desorption treatment is 40-90°C, and the temperature is obtained by high-frequency magnetic induction heating, preferably 45-80°C.

[0114] In this invention, there is no particular limitation on the time of the desorption process, which can be selected according to the actual situation, as long as the purpose of this invention can be achieved.

[0115] According to the present invention, preferably, the CO2 desorption rate of the carbon dioxide absorbent after the first cycle of absorption and desorption is ≥0.5-25 mL / (L×s), more preferably 5-20 mL / (L×s).

[0116] In this invention, under the same adsorption capacity, the desorption rate meets the above-mentioned range of 5-20 mL / (L×s). The faster the desorption rate, the shorter the desorption process time, and the more efficient and energy-saving the entire absorption-desorption process, which is more conducive to achieving efficient carbon capture.

[0117] The present invention will be described in detail below through embodiments.

[0118] Unless otherwise specified, all raw materials used in the examples and comparative examples are commercially available.

[0119] Preparation Example 1 Preparation of unmodified MnFe2O4 Step I: MnFe2O4 nanoparticles were prepared by hydrothermal method. Manganese chloride and ferric chloride in a molar ratio of 1:2 were weighed, dissolved in deionized water, and stirred until completely dissolved to form a 0.17 mol / L precursor solution. Step II: Then, slowly add ammonia water to adjust the pH of the system to 10-11, and continue stirring for 30 minutes to obtain a brown suspension. Transfer the suspension to a polytetrafluoroethylene hydrothermal reactor and react at a constant temperature of 180℃ for 4 hours. After the reaction is completed, allow it to cool naturally to room temperature. Separate the product by centrifugation, redisperse it with deionized water, centrifuge it again, and wash the product repeatedly until the washing liquid is neutral to obtain a suspension of MnFe2O4 nanoparticles with a particle size of 20 nm.

[0120] Carboxyl modification of MnFe2O4 nanoparticles The 20nm MnFe2O4 prepared above was dispersed in an ethanol-water mixed solvent and ultrasonically dispersed for 60 min to form a uniform nanoparticle suspension with a concentration of 5 mg / mL. Citric acid, a carboxyl modifier, was added to the suspension, and the mass ratio of citric acid to MnFe2O4 nanoparticles was controlled. After stirring evenly, the temperature was raised to 70℃ and refluxed for 4 h. After the reaction was completed, the mixture was cooled to room temperature, and the modified product was separated by an external magnetic field. The modified product was washed three times with anhydrous ethanol to remove unreacted free modifier. Finally, it was dispersed in deionized water to obtain carboxyl-modified 20nm MnFe2O4 particles. Based on the total mass of the modified magnetic nanoparticles, the content of the modifier was 1.2 wt%; the content of the unmodified magnetic nanoparticles was 98.8 wt%. The particles exhibited uniform hydrophilic carboxyl loading and excellent dispersibility, and could be directly used for the subsequent preparation of phase change magnetic fluids.

[0121] Preparation Example 2 Following the method of Preparation Example 1, except that by adjusting the precursor solution concentration to 0.28 mol / L and the reaction time to 7 h, MnFe2O4 with a particle size of 80 nm can be obtained.

[0122] Based on the total mass of the modified magnetic nanoparticles, the content of the modifier is 0.75 wt%; the content of the unmodified magnetic nanoparticles is 99.25 wt%.

[0123] Preparation Example 3 Following the method of Preparation Example 1, except that by adjusting the precursor solution concentration to 0.24 mol / L and the reaction time to 7 h, MnFe2O4 with a particle size of 60 nm can be obtained.

[0124] Based on the total mass of the modified magnetic nanoparticles, the content of the modifier is 0.9 wt%; the content of the unmodified magnetic nanoparticles is 99.1 wt%.

[0125] Preparation Example 4 Preparation of Coe2O4 substrate Unmodified CoFe2O4 was prepared according to the method of Preparation Example 1, except that manganese chloride was replaced with an equimolar ratio of cobalt chloride hexahydrate.

[0126] Thiol-based modification of CoFe2O4 nanoparticles The 20nm CoFe2O4 substrate prepared above was dispersed in a mixed solvent of ethanol and deionized water at a volume ratio of 3:1. The dispersion was ultrasonically controlled at room temperature for 90 min to break up particle aggregation, forming a homogeneous and stable suspension with a concentration of 4 mg / mL. The mercapto modifier 3-mercaptopropyltriethoxysilane (MPTES) was added to the suspension, controlling the mass ratio of 3-mercaptopropyltriethoxysilane to CoFe2O4. After stirring until homogeneous, the pH of the system was adjusted to 9-10 using dilute ammonia. The system was heated to 65℃ and refluxed for 5 h. After the reaction was completed, the mixture was cooled to room temperature, and the mercapto-modified product was separated using an external magnetic field. The product was washed three times with anhydrous ethanol to remove unreacted free modifier, and finally dispersed in deionized water to obtain the 20nm mercapto-modified substrate. Based on the total mass of the modified magnetic nanoparticles, the content of the modifier is 0.9 wt% and the content of the unmodified magnetic nanoparticles is 99.1 wt%. The surface of the particles has uniform hydrophilic thiol loading and excellent dispersibility, and can be directly used for the preparation of subsequent phase change magnetofluids.

[0127] Preparation Example 5 The method of Preparation Example 1 is the same, except that in the carboxyl modification of MnFe2O4 nanoparticles, citric acid is replaced with methoxy polyethylene glycol silane, and the amount of methoxy polyethylene glycol silane used is such that, based on the total mass of the finally prepared modified magnetic nanoparticles, the content of the modifier is 1.25 wt%; and the content of the unmodified magnetic nanoparticles is 98.75 wt%.

[0128] Preparation Example 6 Following the method of Preparation Example 1, except that ferric chloride was weighed to form a 0.17 mol / L precursor solution, and the reaction time was adjusted to 4 h to obtain magnetic nanoparticles with a particle size of 20 nm.

[0129] Based on the total mass of the modified magnetic nanoparticles, the content of the modifier is 1.2 wt%; the content of the unmodified magnetic nanoparticles is 98.8 wt%.

[0130] Comparative Preparation Example 1 Following the method of Preparation Example 1, except that by adjusting the precursor solution concentration to 0.38 mol / L and the reaction time to 8 h, magnetic nanoparticles with a particle size of 150 nm can be obtained.

[0131] Based on the total mass of the modified magnetic nanoparticles, the content of the modifier is 0.52 wt%; the content of the unmodified magnetic nanoparticles is 99.48 wt%.

[0132] Comparative Preparation Example 2 Following the method of Preparation Example 1, except that by adjusting the precursor solution concentration to 0.14 mol / L and the reaction time to 3 h, magnetic nanoparticles with a particle size of 10 nm can be obtained.

[0133] Based on the total mass of the modified magnetic nanoparticles, the content of the modifier is 1.35 wt%; the content of the unmodified magnetic nanoparticles is 98.65 wt%.

[0134] Example 1 S1. Dimethylaminopropylacrylamide, N-isopropylacrylamide (NIPAM), and crosslinking agent (N,N'-methylenebisacrylamide, BIS) are mixed, and 2 mM of the first surfactant (hexadecyltrimethylammonium bromide, CTAB) is added for emulsification. Based on the total amount of the polymer monomers, the amount of the first surfactant is 2 mol%. After stirring and reacting for 30 min in a 70°C water bath under nitrogen protection, a water-soluble initiator (2,2'-azobisisobutylammonium dihydrochloride, AAPH) is added, and the reaction continues for 3 h. Based on the total amount of the polymer monomers, the amount of the initiator is 0.85 mol%. After cooling and dialysis purification, a polymer hydrogel with a content of 20 mol% of structural unit A, 75 mol% of structural unit B, and 5 mol% of structural unit C, based on the total amount of the polymer hydrogel, is obtained, with an intrinsic viscosity of 950 mL / g.

[0135] S2. The modified magnetic nanoparticles used were those prepared in Preparation Example 1. Modified magnetic nanoparticles were added to the polymer hydrogel. Based on the total weight of the phase change magnetic fluid, the content of the modified magnetic nanoparticles was 0.1 wt%, and the content of the polymer hydrogel was 99.9 wt%. The mixture was ultrasonically dispersed and compounded according to the above contents to obtain the phase change magnetic fluid of this embodiment.

[0136] In this embodiment, a gas mixture containing CO2 (CO2 content of 12 vol%) was absorbed and desorbed. The absorption process was carried out at a temperature of 35°C for 20 min. The magnetic field frequency used in the desorption experiment was 800 kHz and the magnetic induction intensity was 1800 Gs. A temperature control experiment was conducted using the phase change magnetic fluid from Example 1 as the magnetic induction heating material. Specifically, 20 mL of the phase change magnetic fluid was placed in a glass bubble bottle used for the absorption-desorption experiment. The device was placed inside the induction coil of a high-frequency magnetic induction heating device. The magnetothermal heat generation efficiency was precisely controlled by adjusting the alternating magnetic field parameters. During the process, a gas mixture containing 12 vol% CO2 was passed through to simulate the absorption-desorption process, and the temperature was measured using thermocouples. The horizontal axis represents the heating time. The temperature control process is described in [details omitted]. Figure 1It can be seen that after the system temperature rises to 75℃, precise temperature control of ±2℃ can be achieved within 60s by adjusting the relevant parameters of the alternating magnetic field. The temperature control response is rapid and the adjustment accuracy is high, ensuring that the desorption process is stable and controllable. Taking the phase change magnetohydrodynamic absorbent in Example 1 as an example, the absorption capacity after ten absorption-desorption cycles is shown below. Figure 2 It can be seen that as the number of cycles increases, the absorption capacity of the phase change magnetohydrodynamic absorbent gradually decreases, but the decrease is very small. After 10 cycles, the absorption capacity decrease rate is 9.92%.

[0137] Example 2 The method is the same as in Example 1, except that the magnetic field frequency used in the desorption experiment is 500 kHz and the magnetic induction intensity is 1400 Gs.

[0138] Example 3 The method of Example 1 was followed, except that the modified magnetic nanoparticles prepared in Example 1 were replaced by the modified magnetic nanoparticles prepared in Example 2 in equal mass.

[0139] Example 4 The method of Example 1 was followed, except that the modified magnetic nanoparticles prepared in Example 1 were replaced by the modified magnetic nanoparticles prepared in Example 4 in equal mass.

[0140] Example 5 The method of Example 1 was followed, except that the modified magnetic nanoparticles prepared in Preparation Example 1 were replaced by the modified magnetic nanoparticles prepared in Preparation Example 3 in equal mass.

[0141] Example 6 The method of Example 1 was followed, except that the modified magnetic nanoparticles prepared in Preparation Example 1 were replaced by the modified magnetic nanoparticles prepared in Preparation Example 5 in equal mass.

[0142] Example 7 The method of Example 1 was followed, except that the modified magnetic nanoparticles prepared in Preparation Example 1 were replaced by the modified magnetic nanoparticles prepared in Preparation Example 6 in equal mass.

[0143] Example 8 S1. Dimethylaminopropylacrylamide, N-isopropylacrylamide (NIPAM), and crosslinking agent (N,N-methylenebisacrylamide, BIS) are mixed, and 2 mM of the first surfactant (hexadecyltrimethylammonium bromide, CTAB) is added for emulsification. The amount of the first surfactant is 2 mol% based on the total amount of the polymer monomers. After stirring and reacting for 30 min in a 70°C water bath under nitrogen protection, a water-soluble initiator (2,2-azobisisobutylammonium dihydrochloride, AAPH) is added, and the reaction continues for 3 h. The amount of the initiator is 1.15 mol% based on the total amount of the polymer monomers. After cooling and dialysis purification, a polymer hydrogel with a content of 50 mol% of structural unit A, 40 mol% of structural unit B, and 10 mol% of structural unit C, based on the total amount of the polymer hydrogel, is obtained, with an intrinsic viscosity of 1050 mL / g.

[0144] S2. The modified magnetic nanoparticles used were those prepared in Preparation Example 1. Modified magnetic nanoparticles were added to the polymer hydrogel, with the content of modified magnetic nanoparticles being 0.25 wt% based on the total weight of the phase change magnetic fluid. The mixture was ultrasonically dispersed and compounded according to the above content to obtain the phase change magnetic fluid of this embodiment.

[0145] In this embodiment, a gas mixture containing CO2 (CO2 content of 12 vol%) was absorbed and desorbed. The absorption process was carried out at a temperature of 35°C for 20 min. The magnetic field frequency used in the desorption experiment was 600 kHz and the magnetic induction intensity was 1600 Gs.

[0146] Example 9 Following the method of Example 1, by adjusting the amounts of monomer A, monomer B, and crosslinking agent, a polymer hydrogel was obtained with the following content based on the total amount of the polymer hydrogel: 70 mol% of structural unit A, 26 mol% of structural unit B, and 4 mol% of structural unit C.

[0147] Comparative Example 1 The method of Example 1 was followed, except that the modified magnetic nanoparticles prepared in Preparation Example 1 were replaced by the modified magnetic nanoparticles prepared in Comparative Preparation Example 1 by the same mass.

[0148] Taking the phase change magnetohydrodynamic absorber in Comparative Example 1 as an example, after ten absorption-desorption cycles, the absorption capacity decay rate is 16.85%.

[0149] Comparative Example 2 The method of Example 1 was followed, except that the modified magnetic nanoparticles prepared in Preparation Example 1 were replaced by the modified magnetic nanoparticles prepared in Comparative Preparation Example 2 by the same mass.

[0150] Comparative Example 3 The method is the same as in Example 1, except that the magnetic field frequency used in the desorption experiment is 500 kHz and the magnetic induction intensity is 500 Gs.

[0151] Comparative Example 4 The method is the same as in Example 1, except that in the desorption experiment, the temperature is raised to 75°C in a water bath for desorption.

[0152] Comparative Example 5 The method is the same as in Example 1, except that the dimethylaminopropylacrylamide in Example 1 is replaced with methacrylic acid in equimolar amounts.

[0153] To investigate the effects of magnetic induction intensity and particle size of modified magnetic nanoparticles on desorption efficiency and to analyze the advantages of magnetic field heating desorption over traditional water bath desorption, the heating and desorption data of the examples and comparative examples were compared and analyzed, as shown in Table 1.

[0154] Table 1

[0155] Note: Heating rate, ℃ / s refers to the heating rate of the first cycle of desorption treatment; The final temperature refers to the final temperature of the desorption process in the first cycle; The absorption capacity in mL / L refers to the absorption capacity of the first cycle of absorption treatment; Desorption capacity, mL / L = mLCO2 / L absorbent, refers to the desorption capacity of the first cycle of desorption treatment; Desorption rate, % = desorbed amount / absorbed amount × 100%, refers to the desorption rate of the first cycle of desorption treatment; Desorption rate refers to the CO2 desorption rate of the carbon dioxide absorbent after the first cycle of absorption and desorption; Desorption rate, mL / (L×s) = desorption volume / desorption time; Desorption time = final temperature / heating rate.

[0156] As can be seen from Table 1, compared with the comparative example, in the embodiments of the present invention, under the condition that the particle size of the modified magnetic nanoparticles is the same, the heating effect and desorption rate of the phase change magnetic fluid increase with the increase of magnetic induction intensity. It can raise the temperature in a short time. The faster the heating rate, the earlier the desorption start time, the higher the final temperature, and the more thorough the desorption. Moreover, the desorption speed of the present invention is fast, indicating that the desorption time is short and the desorption response is extremely fast, which can achieve the purpose of rapid desorption, improve the desorption efficiency, and reduce the size of equipment and energy consumption. When the magnetic induction intensity is <1400GS or water bath heating is used, the desorption rate is low. Under the same magnetic induction intensity, only modified magnetic nanoparticles with a particle size between 20-100nm can achieve heating under alternating magnetic field. The comparative example cannot achieve heating and cannot desorb.

[0157] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A phase change magnetofluid, characterized in that, The phase change magnetofluid includes a polymer hydrogel and modified magnetic nanoparticles uniformly dispersed inside the polymer hydrogel. The polymer in the polymer hydrogel has structural unit A as shown in Formula I, structural unit B as shown in Formula II and / or Formula III, and structural unit C provided by a crosslinking agent containing at least two unsaturated double bonds; Equation I; Formula II; Formula III; R1, R5, R6, and R7 are each independently H or C1-C4 alkyl groups, R2 is a C1-C6 alkylene group, R3 and R4 are each independently C1-C4 alkyl groups, and R8 is a C3-C7 alkylene group. The modified magnetic nanoparticles have an average particle size of 20-100 nm. The modified magnetic nanoparticles include a modifier and unmodified magnetic nanoparticles; Based on the total mass of the modified magnetic nanoparticles, the content of the modifier is 0.6-1.3 wt%; the content of the unmodified magnetic nanoparticles is 98.7-99.4 wt%. The modifier is selected from at least one of methoxy polyethylene glycol silane, sodium carboxyethyl silane triol, sulfonated silane coupling agent, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, citric acid, and 3-mercaptopropyltriethoxysilane.

2. The phase change magnetofluid according to claim 1, wherein, R1, R5, R6, and R7 are each independently H or C1-C3 alkyl groups, R2 is a C3-C6 alkylene group, R3 and R4 are each independently C1-C3 alkyl groups, and R8 is a C3-C6 alkylene group. And / or, the crosslinking agent is selected from at least one of N,N'-methylenebisacrylamide, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, divinyl sulfone, and trimethylolpropane triacrylate.

3. The phase change magnetofluid according to claim 1, wherein, The modified magnetic nanoparticles have an average particle size of 20-60 nm. And / or, the unmodified magnetic nanoparticles are selected from at least one of Fe3O4, γ-Fe2O3, MnFe2O4, CoFe2O4 and NiFe2O4.

4. The phase change magnetofluid according to claim 1, wherein, Based on the total amount of the polymer hydrogel, the content of structural unit A is 2-65 mol%; the content of structural unit B is 20-90 mol%; and the content of structural unit C is 2-30 mol%. And / or, the intrinsic viscosity of the polymer hydrogel at 25°C is 300-1800 mL / g.

5. The phase change magnetofluid according to any one of claims 1-4, wherein, Based on the total weight of the phase change magnetic fluid, the content of the polymer hydrogel is 99-99.9 wt%; and the content of the modified magnetic nanoparticles is 0.01-1 wt%.

6. A method for preparing a phase change magnetic fluid according to any one of claims 1-5, characterized in that, The preparation method includes the following steps: S1. In the presence of a solvent, a polymeric monomer, a crosslinking agent containing at least two unsaturated double bonds, a first surfactant, and an initiator are first mixed and then subjected to a copolymerization reaction, followed by post-treatment; the polymeric monomer includes monomer A shown in Formula 1, monomer B shown in Formula 2 and / or Formula 3; Equation 1; Equation 2; Equation 3; R1', R5', R6', and R7' are each independently H or C1-C4 alkyl groups, R2' is a C1-C6 alkylene group, R3' and R4' are each independently C1-C4 alkyl groups, and R8' is a C3-C7 alkylene group. S2. Modified magnetic nanoparticles are added to the product obtained in step S1, and a second mixing is performed to obtain a phase change magnetic fluid. The modified magnetic nanoparticles have an average particle size of 20-100 nm.

7. The preparation method according to claim 6, wherein, R1', R5', R6', and R7' are each independently H or C1-C3 alkyl groups, R2' is a C3-C6 alkylene group, R3' and R4' are each independently C1-C3 alkyl groups, and R8' is a C3-C6 alkylene group. And / or, the amount of monomer A is 2-65 mol; the amount of monomer B is 20-90 mol; and the amount of crosslinking agent is 2-30 mol.

8. The preparation method according to claim 6, wherein, The crosslinking agent is selected from at least one of N,N'-methylenebisacrylamide, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, divinyl sulfone, and trimethylolpropane triacrylate; And / or, the first surfactant is selected from at least one of hexadecyltrimethylammonium bromide, benzalkonium chloride, hexadecylpyridine chloride, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, octadecyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride, tetradecyldimethylbenzylammonium chloride and octadecyldimethylbenzylammonium bromide; And / or, based on the total amount of the polymerizable monomers, the amount of the first surfactant is 0.4-2 mol.

9. The preparation method according to claim 6, wherein, The conditions for the first mixing include: a temperature of 50-90℃ and a time of 10-60 min; And / or, based on the total amount of the polymerizable monomers, the amount of the initiator is 0.1-5 mol%; And / or, the copolymerization reaction conditions include: a temperature of 50-90°C; and a time of 60-300 min.

10. The application of the phase change magnetofluid as described in any one of claims 1-5 as a carbon dioxide absorbent in CO2 emission reduction, carbon capture in biomass utilization processes, or direct carbon capture in air.

11. A method for the absorption and desorption of carbon dioxide, characterized in that, The method includes: Step 1: Absorb CO2-containing gas mixture in the presence of phase change magnetohydrodynamic fluid; Step 2: In the presence of an alternating magnetic field, the phase change magnetofluid processed in Step 1 is desorbed. Step 3: After desorption is completed, stop the alternating magnetic field to complete the first cycle of absorption and desorption. Then repeat steps 1 and 2. The phase change magnetofluid is the phase change magnetofluid according to any one of claims 1-5; The conditions for the alternating magnetic field include: magnetic induction intensity ≥1400GS, and magnetic field frequency of 500-800kHz.

12. The method according to claim 11, wherein, The conditions for the alternating magnetic field include: magnetic induction intensity ≥1500GS, and magnetic field frequency 600-800kHz.

Citation Information

Patent Citations

  • Hollow fiber for separating carbon dioxide, component, preparation method and regeneration method

    CN121737870A